2011
DOI: 10.1002/ijc.26131
|View full text |Cite
|
Sign up to set email alerts
|

AP1B plays an important role in intestinal tumorigenesis with the truncating mutation of an APC gene

Abstract: Recent evidence has suggested that carcinoma is accompanied by the loss of cell polarity. An epithelial cell-specific form of the AP-1 clathrin adaptor complex, AP1B, is involved in the polarized transport of membrane proteins to the basolateral surface of epithelial cells. In our study, we investigated whether AP1B is involved in intestinal tumorigenesis. The cellular polarity of intestinal tumor cells was examined using APC Min/1 mice as an in vivo model and SW480 cells with a truncating mutation in the aden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 34 publications
2
8
0
Order By: Relevance
“…23 Importantly, histological studies suggested that more than 80% of kidney cancers arise from the proximal kidney tubules, [82][83][84] and AP-1B expression is down regulated in mouse models for colon cancer. 85 Furthermore, AP-1B was also found to be reduced in the colon of Crohn's disease patients, 86 and m1B knock out mice suffer from proliferation defects and hyperplasia in their intestine. 87 These observations highlight the importance of AP-1B in epithelial cell maintenance.…”
Section: Expression Pattern Of Ap-1bmentioning
confidence: 42%
“…23 Importantly, histological studies suggested that more than 80% of kidney cancers arise from the proximal kidney tubules, [82][83][84] and AP-1B expression is down regulated in mouse models for colon cancer. 85 Furthermore, AP-1B was also found to be reduced in the colon of Crohn's disease patients, 86 and m1B knock out mice suffer from proliferation defects and hyperplasia in their intestine. 87 These observations highlight the importance of AP-1B in epithelial cell maintenance.…”
Section: Expression Pattern Of Ap-1bmentioning
confidence: 42%
“…AP-1B is downregulated in the colonic epithelium of individuals with Crohn's disease (Takahashi et al 2011). Further, a reduced ratio of tumor to nontumor tissue expression of AP-1B was correlated with nuclear translocation of b-catenin in human colorectal tumor tissue, indicative for a hyperproliferative state (Mimura et al 2012).…”
Section: The Common Recycling Endosomesupporting
confidence: 42%
“…Also E-cadherin was mislocalized to cytoplasmic structures, the E-cadherin -b-catenin interaction was inhibited, and enhanced nuclear translocation of b-catenin was observed (Hase et al 2013). The mislocalization of Ecadherin was also observed in an intestinal epithelial cell line that lacked the mu1B subunit, and the ectopic expression of the latter restored the normal distribution of E-cadherin (Mimura et al 2012). The nuclear translocation of b-catenin was shown to stimulate the preproliferative b-catenin/Tcf4 pathway, and Ap1m2 2/2 mice showed intestinal crypt hyperplasia with villous dysplasia massively enlarged as a result of excessive proliferation of IEC, but the overall length of the small intestine does not seem to be significantly changed.…”
Section: The Common Recycling Endosomesupporting
confidence: 40%
“…Mutation in σ1C discrupts the endosomal translocation of TLR-3 (toll-like receptor 3) and causes a severe autoinflammatory skin disorder called pustular psoriasis [64]. In addition, patients with Crohn's disease (an inflammatory disease of the intestines) display reduced expression of μ1B [60], and intestinal tumour is associated with down-regulation of μ1B [65]. These tissue-specific phenotypes indicate the non-redundant functions of AP-1 subunits: μ1B functions in epithelial cells; σ1B functions in neurons; σ1C functions in skin; and σ1A may function in both neurons and skin.…”
Section: Physiological Roles Of the Ap Complexesmentioning
confidence: 99%